Preliminary findings in a platform‐based MCI trial designed to promote adaptive behaviors. (December 2021) - Gibson, Allison; Kelly, Parsons R; Oaks, Dawn C; Pope, Caitlin N; Rhodus, Elizabeth K; Bardach, Shoshana H; Johnson, Julia; Barber, Justin M; Jicha, Gregory A
Abstract: Background: Receiving a diagnosis of mild cognitive impairment (MCI) may lead to experiences of emotional turmoil stemming from a perceived lack of clarity around diagnosis and prognosis. Previous research has identified several maladaptive behaviors resulting from the diagnosis of MCI that may be targeted for intervention in order to help those with a new diagnosis of MCI best adapt behaviors to maintain functional abilities. Method: A platform‐based MCI trial cohort of individuals, newly diagnosed with MCI from a U.S. Alzheimer's Disease Research Center, was used to pilot a multicomponent interdisciplinary intervention targeting adaptive behavioral responses to the diagnosis of MCI. Thematic analysis was employed with fifteen focus groups across three study groups of 14 participants. After engaging with each of the platform‐based MCI trial components, participants' and their study partner's perceptions of each intervention's acceptability, satisfaction, and compliance across the multicomponent interdisciplinary intervention were assessed. Results: Themes that emerged from the data included a preference towards education, learning new information, and skill development. Both persons with MCI and study partners favored intervention components that were novel to them. They also reported higher satisfaction with activities facilitated by a professional (e.g., social worker, physical therapist, or pharmacist) as opposed to intervention activities that were self‐directed. Participants with MCI and their study partners reported those with impairment's challenges utilizing technology independently, requiring assistance in setting up online medical portals, using wearable exercise trackers and automated pillboxes that represented technology‐dependent components of the intervention. Conclusion: These data suggest that persons, newly diagnosed with MCI, are interested in adaptive, biopsychosocial interventions for persons with MCI. Acceptability, satisfaction, and compliance may be increased when individuals are engaging in learning novel information and skills that are led and supported by professionals. Assistance with and or training in the use of technology‐based interventions may be needed to maximize the impact of such approaches. Further studies exploring the impact on the cognitive and functional decline that may be mediated by adaptive behavioral interventions in persons newly diagnosed with MCI are warranted.